Racial Difference in Symptom Onset to Door Time in ST Elevation Myocardial Infarction. Issue 10 (October 2016) - Bolorunduro, Oluwaseyi; Smith, Blake; Chumpia, Mason; Valasareddy, Poojitha; Heckle, Mark R.; Khouzam, Rami N.; Reed, Guy L.; Ibebuogu, Uzoma N.
Abstract : Background: There are poorer outcomes following ST elevation myocardial infarction in blacks compared to white patients despite comparable door‐to‐reperfusion time. We hypothesized that delays to hospital presentation may be contributory. Methods and Results: We conducted a retrospective analysis of the 1144 patients admitted for STEMI in our institution from 2008 to 2013. The door‐to‐balloon time (D2BT) and symptom‐onset‐to‐door time (SODT) were compared by race. Bivariate analysis was done comparing the median D2BT and SODT. Stratified analyses were done to evaluate the effect of race on D2BT and SODT, accounting for insurance status, age, sex and comorbidities. The mean age was 59±13 years; 56% of this population was black and 41% was white. Males accounted for 66% of this population. The median D2BT was 60 minutes (interquartile range [IQR] 42–82), and median SODT was 120 minutes (IQR 60–720). There was no significant difference in D2BT by race ( P =0.86). Black patients presented to the emergency room (ER) later than whites (SODT=180 [IQR 60–1400] vs 120 [IQR 60–560] minutes, P <0.01) and were more likely to be uninsured ( P <0.01). After controlling for comorbidities, insurance, and socioeconomic status, blacks were 60% more likely to present late after a STEMI (OR 1.6, P <0.01). A subset analysis excluding transferred patients showed similar results. Conclusions: Black patients present later to the ER after STEMI with no difference in D2BT compared to whites. This difference in time to presentation may be one of the factors accounting for poor outcomes in this population.